An Analysis of Potential for Reducing Operational Costs Through The Use of LED Lighting in Indonesian Hotel - Gusti Rahman, Aldo; Juliani, Elsha; Halimi, Burhanuddin (Jurnal Sosial Teknologi, 2024)
Indonesia has significant tourism potential, which drives the growth of the hospitality industry and increasing energy needs. Large energy consumption in hotels, especially in lighting systems, leads to high operational costs and carbon emissions. This study aims to analyze the potential for reducing operational costs through the use of LED lighting at the Bumi Sawunggaling Hotel, Bandung. The methods used include field observation and energy consumption measurement using a Power Quality Analyzer (PQA) for one week, with data taken every 30 minutes. The results of the study show that the hotel's electrical energy consumption reaches 923.45 kWh per week at a cost of IDR 1,334,166. By replacing conventional lighting with LED, hotels can reduce energy consumption by up to 80%, which translates to operational cost savings of 30% or more. The conclusion of this study emphasizes that the application of LED technology not only provides financial benefits but also supports environmental sustainability. The implication of this study is the importance of adopting energy-saving technologies such as LEDs in the hospitality sector as a strategic step to reduce costs and carbon emissions and improve the hotel's reputation as an eco-friendly business, besides that it is very important for Hotel Bumi Sawunggaling to replace its conventional lighting with LED lights to achieve higher energy efficiency. LED lights are known for their superior energy efficiency compared to traditional incandescent lamps or CFL (Compact Fluorescent Lamp) lamps.